2019
DOI: 10.1002/jum.15196
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Ultrasound Features and Biological Properties of Invasive Breast Carcinoma Is Modified by Age, Tumor Size, and the Preoperative Axilla Status

Abstract: Objectives-To investigate the value of ultrasound (US) feature-based models in predicting the proliferation and invasiveness of invasive breast cancer (IBC) and to compare the performance of models based solely on US features with models that combined US features, patient age, tumor size, and axilla status from US.Methods-With ethical approval, 746 patients with a pathologic diagnosis of IBC were reviewed for preoperative clinical, US, and postoperative pathologic data. The proliferation and invasiveness prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Therefore, sonographic features of TNBCs may be an indirect indicator for tumor invasiveness. We have previously reported that sonogram features of breast cancers are reflective of tumor proliferation and invasiveness ( 26 , 27 ). However, in this study, the effect of HIF1A-AS2 and CHRDL1 in determining the growth pattern of the tumor based on US was not studied in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sonographic features of TNBCs may be an indirect indicator for tumor invasiveness. We have previously reported that sonogram features of breast cancers are reflective of tumor proliferation and invasiveness ( 26 , 27 ). However, in this study, the effect of HIF1A-AS2 and CHRDL1 in determining the growth pattern of the tumor based on US was not studied in animals.…”
Section: Discussionmentioning
confidence: 99%
“…The clearest and most complete US images were obtained in DICOM format. The following conventional ultrasound (CUS) features of breast tumors were recorded in concordance with prior studies (12,18) (8) tumor posterior features: no posterior acoustic features, enhancement, shadowing or combined pattern. In addition, suspicious CUS features of axillary lymph node metastasis (LNM) were also evaluated, including rounded hypoechoic node complete or partial effacement of the fatty hilum, the ratio of long axis diameter to short axis diameter < 2, cortical thickening > 3 mm, nonhilar cortical blood flow on color Doppler images, complete or partial replacement of the node with an ill-defined or irregular mass and microcalcifications in the node (25).…”
Section: Clinical Information and Us Conventional Featuresmentioning
confidence: 65%
“…Therefore, LVI has been considered as a major criteria for tumor staging, prognostic prediction, and the treatment choice (3,4). Treatment decisions for T1 breast cancer usually need refer to the presence or absence of lymph node metastasis (5), which is often associated with LVI (1,(5)(6)(7)(8)(9). LVI had been proved as an independent prognostic factor in T1 breast cancer (9,10), and patients with LVI may require more clinical decisions, including surgical type, the margin determination of surgery, and guiding more aggressive neoadjuvant treatment protocols for breast cancer patients (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Rich blood flow is an indicator of the faster growth and higher metabolism of malignant tumors over benign tumors (26,27). Abnormal lymph nodes on US images, a possible indicator of high tumor aggressiveness, could also help detect breast cancers, as previously reported (28,29).…”
Section: Discussionmentioning
confidence: 84%